Patterns of clinic switching and continuity of medication for opioid use disorder in a Medicaid-enrolled population. (1st April 2021) - Cole, Evan S.; Drake, Coleman; DiDomenico, Ellen; Sharbaugh, Michael; Kim, Joo Yeon; Nagy, Dylan; Cochran, Gerald; Gordon, Adam J.; Gellad, Walid F.; Pringle, Janice; Warwick, Jack; Chang, Chung-Chou H.; et al.
Highlights: Prescriber continuity is associated with improved outcomes; however, this has yet to be studied on Medications for Opioid Use Disorder (MOUD). In an analysis of Medicaid enrollees with MOUD, switching MOUD prescribing clinics was common; over 40% of our sample switched at least once. We found that the number of clinic switches for MOUD was associated with adherence, and no relationship with opioid-related overdose. While lack of prescriber or provider continuity is often viewed as problematic, our findings did not indicate this to be the case for MOUD. Abstract: Background: Many persons with opioid use disorder (OUD) initiate medication for opioid use disorder (MOUD) with one clinic and switch to another clinic during their course of treatment. These switches may occur for referrals or for unplanned reasons. It is unknown, however, what effect switching MOUD clinics has on continuity of MOUD treatment or on overdoses. Objective: To examine patterns of switching MOUD clinics and its association with the proportion of days covered (PDC) by MOUD, and opioid-related overdose. Design: Cross-sectional retrospective analysis of Pennsylvania Medicaid claims data. Main measures: MOUD clinic switches (i.e., filling a MOUD prescription from a prescriber located in a different clinic than the previous prescriber), PDC, and opioid-related overdose. Results: Among 14, 107 enrollees, 43.2 % switched clinics for MOUD at least once during the 270 day period. In multivariate regression results, enrollees who were Non-Hispanic black (IRR = 1.43; 95 % CI = 1.24–1.65; p < 0.001), had previous methadone use (IRR = 1.32; 95 % CI = 1.13–1.55; p < 0.001), and a higher total number of office visits (IRR = 1.01; CI = 1.01−1.01; p < 0.001) had more switches. The number of clinic switches was positively associated with PDC (OR = 1.12; 95 % CI = 1.10–1.13). In secondary analyses, we found that switches for only one MOUD fill were associated with lower PDC (OR = 0.97; 95 % CI = 0.95−0.99), while switches for more than one MOUD fill were associated with higher PDC (OR = 1.40; 95 % CI = 1.36–1.44). We did not observe a relationship between opioid-related overdose and clinic switches. Conclusions: Lack of prescriber continuity for receiving MOUD may not be problematic as it is for other conditions, insofar as it is related to overdose and PDC.